A Laboratory‐Based Study of the Priming Effects of Food Cues and Stress on Hunger and Food Intake in Individuals with Obesity. Issue 11 (11th September 2020) - Chao, Ariana M.; Fogelman, Nia; Hart, Rachel; Grilo, Carlos M.; Sinha, Rajita
Abstract : Objective: This study aimed to assess the effects of exposures to food cues and stress on hunger and food intake and examine whether cue responses differ by weight status. Methods: In a laboratory‐based experimental study, participants ( n  = 138) were exposed to stress, neutral, and food cues delivered using an individualized script‐driven imagery task on three separate days. After each cue exposure, participants ate high‐ and low‐calorie snack foods ad libitum (Food Snack Test). Hunger was measured by visual analog scales. Results: Food cues elicited significantly greater increases in hunger compared with neutral and stress stimuli. Cue‐induced hunger did not differ by weight status. Participants consumed a similar number of total calories across stimuli. In response to food cue provocation, participants with obesity consumed [mean (SE)] 81.0% (4.0%) of calories from high‐calorie foods, which was significantly greater than participants with normal weight (63.5%  [3.6%]; P  = 0.001). After the stress cue, participants with obesity consumed 81.4% (4.0%) of calories from high‐calorie foods, which was significantly more than participants with normal weight (70.2% [3.6%]; P  = 0.04). Energy intake from high‐calorie foods did not differ by weight status after the neutral cue. Conclusions: Among individuals with obesity, exposure to food and stress cues shifted consumption to high‐calorie snack foods within a well‐controlled experimental setting.